Persons in relation: an essay on the Trinity and ontology - Awad, Najib George (Fortress Press, 2014)
Introduction -- The modernist condition -- Theological conditioning? -- The postmodernist conditioning -- The "Trinity" and the evaluation of the theological re-conditioning ambition -- Correlation and/as hierarchism, or What we do not need -- Correlation beyond hierarchism -- Perichoresis of "person" and "relation" and Trinitarian theology -- Correlation as relationship model in/with the world -- Conclusion: When theology stands in history